2009
DOI: 10.1016/j.jadohealth.2009.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistencies in Self-Reporting of Sexual Activity Among Young People in Nairobi, Kenya

Abstract: PurposeAccurate and reliable data on the prevalence of adolescents' sexual behavior are paramount for effective sexual and reproductive health intervention. Adolescents' sexual behavior has been widely studied. However, scholars have raised concerns about the accuracy and reliability of self-reported sexual behavior by adolescents. Previous research shows high levels of adolescent sexual activity in urban informal settlements; yet, the accuracy of self-reported sexual experience in these settings is understudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 24 publications
2
52
0
1
Order By: Relevance
“…However, across three waves of surveys, 37% of respondents—12% of girls and 65% of boys—responded inconsistently about the timing of their sexual debut 17. In a Kenyan study of adolescents aged 12–19 years (49% of whom were sexually active), 20% gave inconsistent reports about lifetime sexual intercourse and timing of first sexual intercourse,16 and in South Africa, 40% of sexually active adolescents inconsistently reported lifetime sexual experience 18…”
Section: Introductionmentioning
confidence: 99%
“…However, across three waves of surveys, 37% of respondents—12% of girls and 65% of boys—responded inconsistently about the timing of their sexual debut 17. In a Kenyan study of adolescents aged 12–19 years (49% of whom were sexually active), 20% gave inconsistent reports about lifetime sexual intercourse and timing of first sexual intercourse,16 and in South Africa, 40% of sexually active adolescents inconsistently reported lifetime sexual experience 18…”
Section: Introductionmentioning
confidence: 99%
“…Beguy et al emphasize the importance of ensuring privacy during the interview. 15 Interviewers could benefit from additional training and support to create spaces in settings that are crowded or that lack privacy. Some studies have found that reducing the potential for women aged 15-19 across surveys.…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4] The reporting of the initiation of sexual activity and of the timing of early marriage and childbirth during adolescence may be particularly prone to social desirability bias. Beguy et al's study in Nairobi 15 found that approximately half of adolescents misreported or inconsistently reported sexual experience. The authors argue that while pressure may be felt by young men to overreport sexual experience during adolescence, the opposite is more likely for female respondents, given negative attitudes toward women having sex at a young age or outside of marriage.…”
Section: Methodsmentioning
confidence: 99%
“…(9)(10)(11) In Brazil, no study was identified with this emerging social group. Identifying factors related to the vulnerability of this population for STDs can assist health professionals in the development of interventions to prevent and control these infections among this segment of the population that is, because of its condition of dispersion and urban segregation, is at the margins of public health services.…”
Section: Discussionmentioning
confidence: 99%